The The Kolongan Pigeon Racing Competition In Islamic View: Overview Of Islamic Law - Azmy Ali Muchtar (CV ODIS, 2022)
Keeping birds is a hobby of some humans, one of the birds that are currently in demand to be kept besides chirping birds is the pigeon, this type of bird is often seen flying around community settlements. The phenomenon that occurs is that pigeons are often contested to obtain prizes in the form of money, trophies, etc. This research was conducted in the north Jakarta area, the purpose of this study was to describe the practice of the pigeon racing competition in north Jakarta and then analyze it based on Islamic law. This research uses qualitative research methods whose data collection uses observation, interviews, and documentation. The data analysis technique uses a descriptive method of analysis with an inductive mindset. The results of this study show that the competition is a speed race or also called a pigeon race. At the time of registration, participants are required to pay a lot of money to the committee which is allocated 80% for cash prizes and trophies, and 20% for the committee's honor. When reviewed with Islamic law based on the analysis of researchers, the implementation of the pigeon racing competition organized by some people in Sukapura village, Cilincing district, north of Jakarta is contrary to Islamic law.